Application of remote real-time monitoring to offshore oil and gas operations (Special report (National Academies of Sciences, Engineering, and Medicine (U.S.). Transportation Research Board) ;, 2016)
"TRB Special Report 322: Application of Remote Real-Time Monitoring to Offshore Oil and Gas Operations provides advice to the Bureau of Safety and Environmental Enforcement (BSEE) of the U.S. Department of the Interior on the use of remote real-time monitoring (RRTM) to improve the safety and reduce the environmental risks of offshore oil and gas operations. The report also evaluates the role that RRTM could play in condition-based maintenance (CBM), and how BSEE could leverage RRTM into its safety enforcement program. The report makes recommendations to BSEE about how RRTM could be incorporated into BSEE's regulatory scheme. The recommendations also suggest that BSEE monitor the development of RRTM technologies in relation to risk-based goals governing offshore oil and gas processes"--Provided by publisher